Old City Hall - Rotenberg, Robert, 1953- (Farrar, Straus and Giroux, 2009)
Canada's leading radio show host, Kevin Brace, comes to the door of his luxury condominium with his hands covered in blood and tells the newspaper delivery man: "I killed her." The "her" in question is his young wife, whose body lies in the bathtub with a knife wound through the sternum. So, if he killed her, where's the mystery? That's the question asked by the detectives plowing through what should be an open-and-shut case. With the appearance of strange fingerprints in the apartment, the mystery gets more complex just as it should be getting simpler.